Qur'anic Ethics for Social Media: Insights from Indonesia's Thematic Tafsir - Alfathah, Suryana; Zulaiha, Eni; Fathurrohman, Asep Ahmad (UIN Sunan Gunung Djati Bandung, 2025)
Social media's rapid growth has transformed communication, but neglecting ethical principles rooted in the Quran, like those explained in the Indonesian Ministry of Religious Affairs' Thematic Tafsir, has led to issues such as misinformation, conflict, and privacy breaches. This qualitative library research uses descriptive analysis to highlight the importance of Quran-based ethics in social media. It identifies five key principles: caution and responsibility, verifying information (tabayyun), constructive communication, avoiding prejudice and gossip, and protecting privacy. The study offers actionable guidelines for fostering responsible and ethical social media use, promoting harmony and accountability in digital interactions.